2020
DOI: 10.17645/mac.v8i4.3252
|View full text |Cite
|
Sign up to set email alerts
|

Free Speech Under Pressure: The Effect of Online Harassment on Literary Writers

Abstract: In the perception of writers in Germany, free speech is under strong pressure. A survey study, in which 526 literature writers took part, reveals innumerable aspects of hate speech, online harassment, and even physical assaults. Every second person has already experienced assaults on his or her person and is also aware of attacks on colleagues. Three quarters are concerned about freedom of expression in Germany and complain of an increase in threats, intimidation, and hateful reactions. The research project wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Before investigating individual characteristics that may lead to different perceptions of controversial, (potentially) harmful statements, it is crucial to first define the characteristics of these statements. Previous research usually did not distinguish between different types of speech (e.g., Peter sen, 2021; Wegner et al, 2020) or only focused on the perception of one specific type of discriminatory language, such as hate speech or microag gressive speech (e.g., Sue, 2010), without connecting it to the larger picture of freedom of speech. Even if the discussions surrounding certain contro versial statements do not exclusively revolve around the juxtaposition of freedom of expression and freedom from discrimination, the discourse can mostly be traced to the controversy between these two fundamental freedoms (e.g., Struth, 2019).…”
Section: Types Of (Potentially) Harmful Speechmentioning
confidence: 99%
“…Before investigating individual characteristics that may lead to different perceptions of controversial, (potentially) harmful statements, it is crucial to first define the characteristics of these statements. Previous research usually did not distinguish between different types of speech (e.g., Peter sen, 2021; Wegner et al, 2020) or only focused on the perception of one specific type of discriminatory language, such as hate speech or microag gressive speech (e.g., Sue, 2010), without connecting it to the larger picture of freedom of speech. Even if the discussions surrounding certain contro versial statements do not exclusively revolve around the juxtaposition of freedom of expression and freedom from discrimination, the discourse can mostly be traced to the controversy between these two fundamental freedoms (e.g., Struth, 2019).…”
Section: Types Of (Potentially) Harmful Speechmentioning
confidence: 99%
“…Besides criticizing politics, first and foremost, in the areas of political asylum and European integration (Berbuir, Lewandowsky & Siri, 2015), these voices are often accompanied by racist and Islamophobic stereotyping, insults, and even threats of violence and murder (Paasch-Colberg, et al, 2021a). This has not only intimidated many people and polarized public discourse (Wegner, Prommer & Seidel, 2020), but it has also set the stage for a significant increase in right-wing extremist violence against Muslims, People of Color, and public advocates of immigration (Gehrke, 2021), including arson attacks on refugee shelters, rampages (Munich in 2016, Halle in 2019, Hanau in 2020, and assassination attacks on politicians (namely Henriette Reker in 2015, Walter Lübcke in 2019) who publicly supported liberal refugee politics.…”
Section: Introductionmentioning
confidence: 99%
“…Other genres, like fiction, biographies, and essays, are also nurturing the democratic discourse as well as being dependent on a free and pluralistic public sphere. For this reason, Wegner, Prommer, and Seidel (2020) consider online harassment targeting nonjournalist writers as just a serious threat to democratic discourse as harassment targeting journalists. In their study of German writers, Wegner et al (2020) found that half of the respondents have personal experience of being harassed online.…”
mentioning
confidence: 99%
“…For this reason, Wegner, Prommer, and Seidel (2020) consider online harassment targeting nonjournalist writers as just a serious threat to democratic discourse as harassment targeting journalists. In their study of German writers, Wegner et al (2020) found that half of the respondents have personal experience of being harassed online. For many of these, the attacks have resulted in restrictions in their everyday working life in terms of different forms of self-restraint and even selfcensorship.…”
mentioning
confidence: 99%
See 1 more Smart Citation